Development of Livelihood Skills through School-Based, Agripreneurship Projects Integrating Youth-Adult Partnerships: The Experiences of Youth Partners in Uganda - Stephen C. Mukembo; M. Craig Edwards; Craig E. Watters (Journal of International Agricultural and Extension Education, 2020)
Equipping young people with livelihood skills is essential for positive youth development and empowerment as they transition into adulthood to become productive and engaged members of their communities. In Uganda, which may be the case in other nations of Sub-Saharan Africa, and elsewhere, even though many youth are becoming better educated and graduating from high schools and colleges, a majority of these graduates remain either unemployed or underemployed. Many have not acquired the necessary skills to transition from school to becoming employable and self-reliant. This phenomenon has been attributed to an outdated curriculum that does not meet the needs of contemporary times. Further, the mode of instruction in most of Uganda’s schools is teacher-centeredand provides little room for student engagement and creativity to generate new knowledge, to have authentic learning experiences, or to reflect. Such challenges may be overcome through student-centered learning approaches involving School-Based, Agripreneurship Projects (SAPs) that integrate Youth-Adult Partnerships (Y-APs), as were explored in this study. Evaluation of the students’ experiences through deductive and inductive thematic analysis indicated that they acquired knowledge in poultry science, business, agripreneurship, and life skills, including better communication, leadership, and conflict resolution practices. Longitudinal studies should be conducted to determine the long-term effectiveness and impact of SAPs facilitated by Y-APs on improving youth livelihoods, especially that prepare them with the life skills necessary to be productive citizens. Such research could involve cohort or panel investigations
Keywords: entrepreneurship; positive youth development (PYD); project-based learning (PjBL)